Respuesta :
Answer:
[tex]Price\: of \:soda\: is:\:P_s= \frac{100d}{2h+s}[/tex]
Step-by-step explanation:
Let
[tex]P_s = cost\: of\: soda[/tex]
[tex]P_h=cost \:of\:hotdog[/tex]
in dollars.
Then we know that
[tex]P_h=2P_s[/tex]
And if the vendor makes total of d dollars:
[tex]hP_h+sP_s=d[/tex]
Now substitute the value of [tex]P_h=2P_s[/tex] into this equation and get;
[tex]2hP_s+sP_s=d[/tex]
[tex]=P_s(2h+s)=d.[/tex]
[tex]\therefore P_s= \frac{d}{2h+s}[/tex]
Now this price is in dollars, and to convert it to cents we just multiply it by 100.
[tex]\boxed{\therefore P_s= 100\frac{d}{2h+s} }[/tex]
Answer:
The required cost of a soda is [tex]y=100\frac{d}{(2h+s)}[/tex] cents.
Step-by-step explanation:
Given: A vendor sells [tex]h[/tex] hot dogs and [tex]s[/tex] sodas. If a hot dog costs twice as much as a soda.
Let the cost of a hot dog be [tex]x[/tex] dollars and cost of a soda be [tex]y[/tex] dollars.
According to question,
Cost of a hot dog is twice as much as cost of a soda.
[tex]x=2y[/tex] ...... (1)
Now, total cost of hot dogs and soda given by [tex]x\times h+y\times s=d[/tex] dollars.
[tex]2y\times h+y\times s=d\\[/tex] ( From equation 1 )
[tex]y(2h+s)=d\\[/tex]
[tex]y=\frac{d}{2h+s}[/tex]
Therefore, cost of a soda is [tex]y=\frac{d}{(2h+s)}[/tex] dollars.
As we know that,
[tex]1[/tex] dollar [tex]=100[/tex] cents
Hence, Cost of a soda is [tex]y=100\frac{d}{(2h+s)}[/tex] cents.
For more information:
https://brainly.com/question/21120154?referrer=searchResults